Primary teacher educators' practices in and perspectives on inquiry-based science education: insights into the Australian landscape. Issue 3 (3rd April 2021) - Fitzgerald, Angela; Pressick-Kilborn, Kimberley; Mills, Reece
ABSTRACT: Initial teacher education (ITE) providers prepare graduates to be effective classroom practitioners, but there is little contemporary research capturing what this preparation actually looks like for primary (elementary) science education in Australia. Drawing on a broader study, this paper reports on teacher educators' practices and perspectives about inquiry-based science education using questionnaire and interview data. The findings unpack five themes that make sense of how inquiry-based science education is understood and enacted in ITE. Implications are discussed in the form of 'tensions' for both inquiry-based science teaching and learning with recommendations for navigating these tensions suggested.